O atendimento educacional especializado e o processo de escolarização dos alunos com deficiência - Silva, Mara Cristina Fortuna da (2015)
This research aims to understand the role of the Educational Service Specialist (ESA) in the educational process of students with disabilities in regular schools, from the perspective of teachers in this service. This research supported this in the National Policy for Special Education in the Perspective of Inclusive Education (2008) and based on the approach of Historical-Cultural Psychology, through Vygotsky's studies (2010). The survey was conducted with 31 teachers from Educational Service Specialized Service (SAEDE) of state schools in the city of Chapecó / SC, through application of structured questionnaires with open questions, closed and mixed, and five oral interviews with five teachers the AEE five selected schools from state schools. The collected data were analyzed using content analysis with a view to Bardin (1994, 2009, 2011). The results show that most teachers are licensed in Pedagogy and admitted by temporary contracts, and this type of admission, one of the factors that prevent them from pursuing the development of learning of students in the ESA, in addition to this type of contract, indicate signs sidelined as there are priorities for competitions for teachers of regular schools. The data also show that the majority of teachers do not recognize the role of ESA as a means of developing the higher psychological functions of students with disabilities, while indicating the completion of activities with this proposal. However, consider that this service focus on capabilities and not on the student's disability. Another factor highlighted appointed by the teachers are the difficulties encountered so to take effect the development of student learning disabled, including: lack of support from school staff and teachers, teachers' resistance in receiving advice of ESA's teacher, the high number of services to students diagnosed with Deficit Hyperactivity Attention Disorders (ADHD) and treated at ESA. The findings found in this research indicate that the role of the EEA goes beyond complement to school learning of students with disabilities, but collaborate at a global sense of this student. However, it still indicates a great need for further information and knowledge regarding the work done at ESA, as a taxpayer in the process of education of students with disabilities.